Potential of radiological methods in gastroenterology - Z. A. Lemeshko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To analyze reports and publications devoted to radiological methods at investigation and treatment of gastroenterological patients and to acquaint gastroenterologists, radiologists, doctors of other specialties with potential of these methods.Summary. Modern concepts of radiological methods of investigation and their application at detection and differential diagnostics of gastroenterological diseases are presented. Significant input of radiological methods to assessment of treatment approach at therapeutic and surgical pathology of digestive system, necessity of utilization of radiological methods at noninvasive medical manipulations, classical surgical interventions, long-term monitoring by patients is shown.Conclusion. Expansion of range of issues solved by radiological methods at investigation of patients with digestive diseases is marked. Priority of noninvasive ways of diagnostics is indicated.